Upland Rice Growth after Low-Input Amendments on Upland Soil in West Kalimantan, Indonesia - Sutarman Gafur; Ismahan Umran (JOURNAL OF TROPICAL SOILS, 2019)
Upland soils in West Kalimantan used for agricultural activities reach about 483,077 hectares. However, this land potential is not yet optimally exploited due to poor soil fertility. To increase its productivity, there is a need to invent technology packages that are not only effective but also efficient. This research is designed to study the growth of upland rice and the changes in certain soil properties after low-input treatment applications. This research used a Completely Randomized Design. There were 6 treatments and 4 replications. The treatment levels were P0 (no treatment), P1 (7tons of cow manure/ha + 300 kg NPK compound), P2 (15tons of cow manure/ha + 300 kg NPK compound), P3 (7tons of compost/ha + 300 kg NPK compound), P4 (15tons of compost/ha + 300 kg NPK compound), and P5 (600 kg/ha NPK compound). Parameters included plant height and dry weight, NPK absorptions, soil pH, organic C content, and NPK contents after soil treatment. The results showed that upland rice responded well to low-input amendment treatments compared to that of grow-in soil with no input treatments. Both the treatments using 15 tons of cow manure and 15 tons of rice straw compost per hectare, each plus 300 kg of NPK, were suggested to be further research topics for treatments in upland soil of West Kalimantan.